IMPLEMENTASI PROGRAM PELATIHAN DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN PADA BANK ICB BUMIPUTERA PEKANBARU - Atikah, Fadilah; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research is: (1) to find out and analyse the training program (2) to find out and analyse the employees performance (3) to determine the influence of the training program with employees performance in bank ICB Bumiputera Pekanbaru. This research was conducted in the offices of Bank ICB Bumiputera Pekanbaru that is located on jalan Sudirman.The research method used was quantitative. With the object of research is the Bank ICB Bumiputera Pekanbaru. With the method of data collection by means of Quisioner and interviews. Data analysis techniques using Simple Linear regression analysis. With the results of the research there is training program influences with employees performance in bank ICB Bumiputera Pekanbaru of 78,0 Percent.Keywords: Training program, employees performance.